Nano Tips for Navigating Bias and Stereotypes as an Asian American Professional with Diana YK Chan. - YK Chan, Diana (linkedin.com, 2023)
Personal branding and confidence coach Diana YK Chan shares lived experiences and tips on how to deal with Asian stereotypes and bias in the workplace, and with scripts to respond.